INTEGRATING BLOCKCHAIN IN EDUCATIONAL MANAGEMENT SYSTEMS: TRANSPARENCY AND ACCOUNTABILITY IN PUBLIC ADMINISTRATION - Nadry, Zabihullah; Sirat, Abdul Wali; Hakimi, Musawer; Quraishi, Tamann (Jurnal Ilmiah Dinamika Sosial, 2025)
Blockchain application in educational administrative systems has emerged as a possible way to enhance transparency, accountability, and efficiency in administrative and academic operations. Despite its growing relevance, a systematic review of blockchain applications across public administration and the field of education is not abundant. With this inquiry, we intend to deliver an extensive literature review to highlight trends, benefits and limitations regarding the use of blockchain technology in educational governance and management in the interest of systematically reviewing and reporting empirical studies through the PRISMA methodology. A Systematic Literature Review (SLR) approach, consisting of synthesizing relevant literature according to the specification outlined by the PRISMA framework, resulted in 25 quality studies that were published between 2016-2025, selected from various peer-reviewed journals contained within the databases of IEEE Xplore, ScienceDirect, SpringerLink, Emerald Publishing, MDPI, and Wiley Online Library. Results of a thematic analysis revealed three significant themes: (1) blockchain enables secure verification of credentials, exchange of credits and green learning teaching learning processes; (2) blockchain supports public sector reform, enhancing transparency and accountability within government bodies; and (3) realization of blockchain technology has been hindered by concerns of cost, scalability, privacy and, resistance to implementation. Overall, this study suggests that blockchain can be catalytic for scaling teaching, learning and administrative processes in education and highlights the need for strategic frameworks in order to overcome technological and organizational challenges.